ACCULTURATION OF TRADITIONAL AND ISLAMIC LAW IN THE PRACTICE OF INHERITANCE DISTRIBUTION OF THE MANDAILING TRIBE OF NORTH SUMATRA - Nur Saniah; Ahmad Bastomi (Fenomena, 2022)
Acculturation of al-adat and Islamic law is a means to determine the extent to which Islamic law and local custom come into contact with the life practices of the Mandailing Tribe community of Islam without any contradictions. This research is empirical research with descriptive analysis. Research data were collected using observation and interview methods, then analyzed using content analysis methods. The results of this study indicate a synergism of the Mandailing tribal community, which adheres to a patrilineal kinship system to carry out Islamic law in parallel and local customs. The practice of sharing inheritance in the Mandailing tribal community is carried out traditionally by containing Islamic values. This practice is a realization of the philosophy of the Mandailing tribal community as "Ombar do adat dot ugama" and "The Customary Country of Obedience to Worship" as a forum to unite the Islamic legal and the customary law system. The acculturation of Islamic law and customary law in sharing inheritance in the Mandailing community shows that Islamic law can be dialogued with the customs that live in the community while still realizing the values of justice and benefit. Inheritance practice that dialogues Islamic law and the customary law of the Mandailing tribe in the inheritance distribution process, making daughters as heirs, presenting religious and traditional leaders during the inheritance distribution process, while maintaining undivided assets in the form of heirloom houses and objects for the son (youngest).